2019
DOI: 10.21203/rs.2.275/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Diagnostic Accuracy of an Intelligent and Automated Fundus Disease Image Assessment System with Lesion Quantitative Function (SmartEye) in Diabetic Patients

Abstract: Background With the diabetes mellitus (DM) prevalence increasing annually, the human grading of retinal images to evaluate DR has posed a substantial burden worldwide. SmartEye is a recently developed fundus image processing and analysis system with lesion quantification function for DR screening. It is sensitive to the lesion area and can automatically identify the lesion position and size. We reported the diabetic retinopathy (DR) grading results of SmartEye versus ophthalmologists in analyzing images captu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…FFA can clearly reflect the pathology of the blood vessels in the retina fundus, but it takes a long time and may cause a variety of adverse reactions [4,5]. Therefore, compared with FFA, fundus photography of the retinal is often used in the researches of fundus disease diagnosis algorithms, which makes it possible to carry out large-scale fundus disease screening rapidly and efficiently, and is conducive to the early detection and treatment of DR patients [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FFA can clearly reflect the pathology of the blood vessels in the retina fundus, but it takes a long time and may cause a variety of adverse reactions [4,5]. Therefore, compared with FFA, fundus photography of the retinal is often used in the researches of fundus disease diagnosis algorithms, which makes it possible to carry out large-scale fundus disease screening rapidly and efficiently, and is conducive to the early detection and treatment of DR patients [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The model predicted the 5-level grades of international diabetic retinopathy and achieved an AUC of 0.986, a sensitivity of 0.971, a specificity of 0.923 on the EyePACS validation dataset [9]. In 2019, Xu et al [10] evaluated DR based on red lesions and bright lesions of fundus images. The model was tested with 19,904 fundus images.…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement in computer vision and artificial intelligence, techniques for measuring eye characteristics using fundus photography have been developed. These techniques can be used to detect eye diseases such as diabetic retinopathy or optic nerve hypoplasia [17,18]. In this study, we detect eye conditions by using fundus photography and the algorithm reported in our previous article [17].…”
Section: Methodsmentioning
confidence: 99%
“…These techniques can be used to detect eye diseases such as diabetic retinopathy or optic nerve hypoplasia [17,18]. In this study, we detect eye conditions by using fundus photography and the algorithm reported in our previous article [17]. We use the values obtained with the algorithm, which are reported in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Early results showed high diagnostic sensitivity and specificity of such systems in DR screening programs in many countries. [ 33,34,35] Limitations of the study concern mostly data used. NHF's data include data provided to all insured people in Poland (in 2017 approx.…”
Section: P R E P R I N Tmentioning
confidence: 99%